Prognostic impact of CT-derived muscle-adipose index change in patients with inoperable esophageal squamous cell carcinoma undergoing chemoradiotherapy - Zhang, Bingyi; Guo, Dong; Cai, Yuanyuan; Wang, Xiaoxiao; Wei, Xinyue; Li, Yang; Wang, Xiaoli; Li, Jianwen; Hao, Furong (Frontiers in Oncology, 2025)
BackgroundThe muscle-adipose index (MAI), a novel nutritional parameter for assessing body composition, has emerged as a potential prognostic indicator. This study aimed to research MAI and its longitudinal changes before and after chemoradiotherapy (CRT) and to evaluate the prognostic implications of these changes in patients with inoperable esophageal squamous cell carcinoma (ESCC).MethodsThis retrospective cohort included 180 ESCC patients treated with CRT (2020-2024). MAI was derived from CT-based quantification of skeletal muscle and subcutaneous adipose tissue at the third lumbar vertebra(L3). Baseline (preMAI), post-treatment (postMAI), and their longitudinal changes (ΔMAI) were analyzed. Optimal cutoff values for MAI imbalance were determined using X-tile software. Overall survival (OS) and progression-free survival (PFS) were assessed using Kaplan-Meier and Cox regression analyses.ResultsAmong 180 enrolled patients, 111 (61.7%) patients died during follow-up (median OS:23.0 months; median PFS:16.0 months).PreMAI and postMAI demonstrated statistically significant associations with OS (preMAI: HR = 5.934,95%CI=3.943-8.929, P<0.001; postMAI: HR = 9.123,95%CI=5.769-14.426, P<0.001) and PFS (preMAI: HR = 5.316, 95%CI=3.583-7.889, P<0.001; postMAI: HR = 8.008, 95%CI=5.213-12.303, P<0.001). The 0 group (prebalance-postbalance) demonstrated significantly better survival outcomes than the remaining groups, both in terms of OS (HR = 9.454, 95%CI=5.830-15.331, P<0.001) and PFS (HR = 8.444, 95%CI=5.360-13.303, P< 0.001). Multivariate analysis confirmed ΔMAI as an independent prognostic factor for OS (HR = 2.953, 95%CI=1.070-8.151, P = 0.037) and PFS (HR = 3.204, 95%CI=1.166-8.806, P = 0.024).ConclusionCT-derived MAI was a robust prognostic biomarker in ESCC. These findings highlighted the clinical utility of MAI for risk stratification and personalized therapeutic strategies in inoperable ESCC patients.